Ecotoxicological Impact of the Bioherbicide Leptospermone on the Microbial Community of Two Arable Soils - Romdhane, Sana; Devers-Lamrani, Marion; Barthelmebs, Lise; Calvayrac, Christophe; Bertrand, Cédric; Cooper, Jean-François; Dayan, Franck E.; Martin-Laurent, Fabrice (Frontiers in Microbiology, 2016)
The ecotoxicological impact of leptospermone, a β-triketone bioherbicide, on the bacterial community of two arable soils was investigated. Soil microcosms were exposed or not (control, 0×) to leptospermone applied at 1× or 10× recommended dose. Leptospermone was moderately adsorbed to both soils (i.e.: Kfa  1.2 and Koc  140 ml.g-1). Dissipation of leptospermone was lower in sterilized than in unsterilized soils suggesting that it was mainly influenced by biotic factors. Within 45 days, leptospermone disappeared almost entirely from one of the two soils (i.e. DT50 < 10 days), while 25% of the leptospermone remained in the other. The composition of the microbial community assessed by qPCR targeting 11 microbial groups was found to be significantly modified in soil microcosms exposed to leptospermone. Pyrosequencing of 16S rRNA gene amplicons showed a shift in the bacterial community structure and a significant impact of leptospermone on the diversity of the soil bacterial community. Changes in the composition as well as in the α- and β-diversity of microbial community were transient in the soil able to fully dissipate the leptospermone. They were persistent in the soil where leptospermone remained. To conclude the bacterial community of the two soils was sensitive to leptospermone and its resilience was observed only when leptospermone was fully dissipated.